PERAN PERHIMPUNAN PELAJAR INDONESIA (PPI) DALAM UPAYA PERLINDUNGAN TENAGA KERJA INDONESIA DI MALAYSIA - Rahmat Saleh; Dian Wahyu Utami; Irin Oktafiani (Research Centre for Population, Indonesian Institute of Sciences, 2019)
International migration is usually motivated by economic reasons. However, many people also migrate overseas to continue studies in higher-level education. This paper analyses the role of Indonesian students abroad, especially those who are members of the Indonesian Student Association (PPI) in protecting Indonesian workers (TKI). The research is focused on PPI in the country with the highest number of Indonesian migrant workers, namely Malaysia. This study applied a qualitative approach to collect primary and secondary data. Primary data was collected through interviews, and secondary data was gained through literature review. The research shows that PPI, as an agent of change, has a role in protecting migrant workers. The PPI has various kinds of contributions such as expressing ideas and discourses to protect international migrant workers, becoming a mediator (in solving conflicts involving the workers), facilitating shelter, providing repatriation assistance, legal assistance and advocacy, as well as economic empowerment and education activities for migrant workers and their families.